2018
DOI: 10.1097/inf.0000000000001820
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Visiting and Isolation Policies in Neonatal Units: A U.K. Nationwide Survey

Abstract: Global pandemics, such as H1N1, are a major risk for neonatal patients. We surveyed U.K. tertiary and district neonatal units about visiting and infection control policies relating to viral respiratory infections. There was marked variation with visiting policies, tertiary units being more restrictive. Isolation, screening, and outbreak management of infected babies was highly variable posing a risk in future pandemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Our data suggest that a combination of IP&C strategies including excluding family members with illnesses, excluding visitors less than 12 years of age year-round, and screening asymptomatic infants in close proximity to an infant with a respiratory virus decreases the transmission event rates, although our sample may have been too small to assess the sustained effect of the interventions over time. Excluding sibling visitors and screeningexposed infants are practices that have been implemented in some NICUs in the U.K [25] and others have shown that restricting sibling visitors reduced RSV [26]. While these interventions were associated with reducing transmission events in our NICU, they did not eliminate respiratory viruses.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our data suggest that a combination of IP&C strategies including excluding family members with illnesses, excluding visitors less than 12 years of age year-round, and screening asymptomatic infants in close proximity to an infant with a respiratory virus decreases the transmission event rates, although our sample may have been too small to assess the sustained effect of the interventions over time. Excluding sibling visitors and screeningexposed infants are practices that have been implemented in some NICUs in the U.K [25] and others have shown that restricting sibling visitors reduced RSV [26]. While these interventions were associated with reducing transmission events in our NICU, they did not eliminate respiratory viruses.…”
Section: Discussionmentioning
confidence: 78%
“…As support for the importance of this priority, during this same time period, 46 central line-associated bloodstream infections occurred in our NICU compared with the 86 episodes of respiratory viral detection described in this study. However, optimal IP&C strategies for respiratory viruses in the NICU population are unknown and highly variable as demonstrated in a nationwide study conducted in the United Kingdom [25]. Our data suggest that a combination of IP&C strategies including excluding family members with illnesses, excluding visitors less than 12 years of age year-round, and screening asymptomatic infants in close proximity to an infant with a respiratory virus decreases the transmission event rates, although our sample may have been too small to assess the sustained effect of the interventions over time.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of good quality evidence to inform NICU policies regarding viral transmission prevention measures, screening protocols, and infection control as well as isolation procedures following identification of cases [7]. This has been observed with wide variations in the UK NICU policies [4]. During the pandemic influenza seasons, our hospitals trust like others implemented a policy of restricting visiting to parents only, reducing the incidence of VRTI by 39% [6].…”
Section: Discussionmentioning
confidence: 99%
“…On the NICU, VRTIs are hospital-acquired and so are most likely to originate from staff or visitors. In the UK, infection control and visiting policies relating to VRTIs vary widely [4]. The inpatient burden of hospital-acquired VRTIs in the NICU, compared with that of the local population in hospital with a VRTI, has not previously been established.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the significance of clinically asymptomatic VRTI remains unclear. Overall, evidence appears insufficient to inform clinicians and policy makers concerning indications for virus testing and visiting policies (6,8). Aim of this study was to evaluate the frequency of symptomatic and asymptomatic VRTI in our family-centered NICU.…”
Section: Introductionmentioning
confidence: 99%